Pupil Size Associated with the Largest Iris Volume in Normal Chinese Eyes. (27th December 2018) - Li, Shuning; Jiang, Jing; Yang, Yiquan; Wu, Gewei; Li, Shi-Ming; Thomas, Ravi; Wang, Ningli
Abstract : Background . To determine the range of pupil size that has the largest iris volume in normal eyes. Methods . 31 healthy adult Chinese volunteers underwent swept-source anterior segment OCT examination in both eyes. Pilocarpine 1% was instilled in a randomly selected eye (eye with induced miosis (ME)) of each participant to obtain iris volume (IV) measurements over a range of pupil sizes. OCT was performed prior to and one hour after pilocarpine in both ME and fellow eye (FE). Iris volume (IV), anterior chamber volume (ACV), anterior chamber depth (ACD), and pupil size (PS) were recorded. A scatter plot was used to depict the association between each pupil size and IV. Results . The pupillary sizes for which IV was recorded in ME and FE ranged from 1.161 mm to 6.665 mm. The mean IV increased with miosis in both ME and FE; in 13 eyes, IV decreased with a decrease in pupillary size. PS between 3.812 and 6.665 mm was associated with an increase in IV, while PS between 3.159 and 5.54 mm was associated with a decrease. The relationship between PS and IV was in the shape of a downward parabola and was modeled using a quadratic equation ( y = −1.3121 x 2 + 8.8429 x + 16.423, R 2 = 0.26886). The largest IV occurred at PS between 3 and 4 mm. Conclusions . The relationship between PS and IV in this study was in the shape of a downward parabola. The largest IV was recorded at a pupillary size between 3 and 4 mm. This trial is registered withChiCTR-ROC-17013572 .